An international online survey on extent of phubbing and its correlates - Shah, Bigya; Kuppili, Pooja Patnaik; Navin, Karthick; Shoib, Sheikh; Syarif, Zulvia Oktanida; Thapa, Jeevan (Journal of Psychiatrists’ Association of Nepal, 2024)
Introduction: Phubbing can be described as an individual looking at his or her mobile phone during a conversation with other individuals, dealing with the mobile phone and escaping from interpersonal communication. Being a new concept, research on its correlates is limited. The aims of the study were to find the extent of phubbing and its correlates. Material & Methods: It was an online survey through Google forms with cross-sectional design and convenience sampling. Those above 18 years who were willing to participate and provided consent were included. The questionnaire included socio-demographic and clinical details, Patient health questionnaire (PHQ-4), and couples ‘satisfaction index (CSI) scale. Descriptive statistics, group comparisons, and Pearson's correlation were done. Results: 904 participants (463 from India, 224 from Nepal, 132 from Indonesia, others 85) were included in the study. 2.3% had a higher likelihood of phubbing. The total phubbing score showed a statistically positive significant correlation with the duration of internet use (p<0.001), social media use (p<0.001), and total PHQ score (p<0.001) and statistically negative significant correlation with duration of the relationship (p=0.004), and total CSI score (p<0.001). Phubbing was significantly higher among males (p=0.044), those educated less than graduate level (p=0.012), in a relationship (p=0.009), using psychoactive substances frequently (p=0.001), dissatisfied with the relationship (p=0.024), and among those with anxiety (p<0.001) and depressive symptoms (p<0.001). There was no difference in phubbing in between the countries (p value= 0.193). Conclusion: Prevention and management of phubbing should target those at risk. Focusing on reducing phubbing will improve mental health, couples’ relationship, and reduce excessive internet and social media use.